Angiomatous meningioma with cystic change: 4 cases report and literature review - Yuchen Sun; Shengwei Yang; Sheng Chang; Huijuan Wang (Egyptian Journal of Neurosurgery)
Abstract Background Meningioma is a common intracranial tumor in clinical practice, most of which are benign. Angiomatous meningioma (AM) is a rare subtype of meningioma, and AM with cystic change is even rarer. Case presentation In view of the lack of research reports on AM with cystic change, this report introduces 4 cases of AM with cystic change admitted to the Department of Neurosurgery of the Second Hospital of Hebei Medical University and Zhangjiajie People’s Hospital in the past five years, in order to provide some help for the clinical diagnosis and treatment. Conclusions AM with cystic change, a rare combination, poses significant challenges for preoperative diagnosis through imaging. However, distinctive imaging features can assist in the diagnosis, thereby facilitating thorough surgical preparation. Surgical resection is the preferred treatment approach, and extensive preparations to manage potential severe bleeding during the operation are necessary. Diagnosis is confirmed based on postoperative histopathology. Given the limited number of reported cases, further research is required.